Increased off-target binding of [18F]florbetaben in the skull of women with reduced skull density - Hipp, Noah; Young, Kim Lea; Apostolova, Ivayla Ilieva; Klutmann, Susanne; Hardewig, Iris; Koglin, Norman; Gallinat, Jürgen; Buchert, Ralph (Nuklearmedizin - NuclearMedicine, 2024)
Aim To investigate the relationship between off-target binding of the amyloid tracer [18F]florbetaben (FBB) in the skull and skull density.Methods Forty-three consecutive patients were included retrospectively (age 70.2±7.5y, 42% females, 65% amyloid-positive). For each patient, CT skull density (in Hounsfield units) and (late) FBB uptake in the skull were obtained using an individual skull mask generated by warping the skull tissue probability map provided by the statistical parametric mapping software package (version SPM12) to the native patient space. Skull FBB uptake (mean of the 10% hottest voxels) was scaled to the individual median FBB uptake in the pons. The association between skull FBB uptake and skull density was tested by correlation analyses. Univariate analysis of variance (ANOVA) of skull FBB uptake with dichotomized skull density (low: ≤ median, high), sex (female, male) and amyloid-status (positive, negative) as between-subjects factors was used to assess the impact of sex and amyloid status.Results There was a significant inverse correlation between skull FBB uptake and skull density (Pearson correlation coefficient -0.518, p < 0.001; Spearman rho -0.321, p = 0.036). The ANOVA confirmed the bone density effect on the FBB uptake in the skull (p = 0.019). In addition, sex (p = 0.012) and density*sex interaction (p = 0.016) had a significant impact. Skull FBB uptake was significantly higher in females with low skull density than for all other combinations of sex and skull density. Amyloid status did not reach statistical significance (p = 0.092).Conclusion Off-target binding of FBB in the skull is inversely associated with skull density. The relationship is mainly driven by females. Amyloid status does not have a major impact on skull FBB binding.
Keywords: amyloid PET; off-target binding; skull; human; [18F]florbetaben